"Vivid mathematics" as a general vector of multidisciplinary STEM education for future aerospace engineers. (January 2021) - Mayorova, Vera I.; Grishko, Dmitriy A.; Leonov, Victor V.
Abstract: At present, a high school graduate aimed at becoming an aerospace engineer faces the need for a deeper study of STEM disciplines already in senior classes. Successful comprehension of such disciplines should be based, in addition to personal interests and propensity to study, on additional online courses, visits of laboratories at universities and facilities, and a direct involvement in personal projects with subsequent presentation thereof. However, our experience in practical educational activities in senior classes shows that even pupils of physics-mathematics schools experience difficulties in solving interdisciplinary problems. As a result, this is manifested in the inability to analyze integrated problems and reduce them into a set of solutions, which were properly studied in school. Analytical skills will be required from future students of aerospace universities for working on their first projects. Hence during senior classes, school students have to gain skills in fast adaptation of a known material to problems with unfamiliar conditions. The primary purpose of such tasks is the demonstration of how some or other solutions can go beyond habitual frames of its subject field. High school students should be able to see that a problem, which at first sight seems very demanding can be solved by fairly standard mathematical methods if one has an idea about the underlying physical principles. With the help of several exercises that have real-world settings and thus are easily remembered, the authors show how links between abstract mathematics and the real world can be highlighted. While dealing with such tasks, associative images are formed in heads of future engineers, which later may become instrumental in solving ill-posed problems. Highlights: Freshmen of aerospace university: math-reality gap shows up while working on their first projects. "Vivid Math" concept is proposed to enhance knowledge in STEM among high school pupils. The concept is based on math application in inter-disciplinary life-related complex problems. School "Science project": a tool for learning and motivation to choose STEM related profession. Exciting examples of 4 types of "Vivid Math" complex tasks are given.